"Water‐in‐Eutectogel" Electrolytes for Quasi‐Solid‐State Aqueous Lithium‐Ion Batteries. Issue 23 (6th May 2022) - Hou, Xu; Pollard, Travis P; He, Xin; Du, Leilei; Ju, Xiaokang; Zhao, Wenguang; Li, Meirong; Wang, Jun; Paillard, Elie; Lin, Hai; Sun, Jingyu; Xu, Kang; et al.
Abstract: The development of high safety lithium‐ion batteries (LIBs) is greatly impeded by the flammability and leakage concerns of typical organic solvent‐based electrolytes. As one of the alternative classes of electrolytes, hydrogel electrolytes exhibit high safety, high flexibility, low cost, and are benign to the environment. However, the narrow electrochemical stability window (ESW) of typical hydrogel electrolytes restricts the operating voltage of battery cells. Here, a new class of "water‐in‐eutectogel (WiETG)" electrolyte is reported, fabricated by combining a hydrogel with a "deep eutectic solvent" (LiTFSI in acetamide). The obtained WiETG electrolyte exhibits non‐flammability, high ionic conductivity, and a wide ESW. LiMn2 O4 ||Li4 Ti5 O12 cells with the WiETG electrolyte exhibit good cycling stability, high flexibility, and high safety. This newly developed WiETG electrolyte not only broadens the ESW of typical hydrogel electrolytes, but also opens a new perspective on future directions and guidance for the design of high safety electrolytes for flexible LIBs and beyond. Abstract : This work introduces a new type of "water‐in‐eutectogel" electrolyte (WiETG) with high safety, good stretchability, and high ionic conductivity. This enables LiMn2 O4 ||Li4 Ti5 O12 full cells with WiETG to exhibit high energy efficiency (86%, 1 C), good long‐term cycle stability (89% after 500 cycles at 5 C), as well as good low temperature performance.